Introduction to crop husbandry : including grassland - Lockhart, J. A. R. (Pergamon, 1988)
Since 1983, when the last edition was published, there have been important new developments in crop husbandry methods as well as an increasing awareness of political and ecological pressures. These pressures have resulted in considerable changes in crop husbandry and the new edition reflects these changes by updating all chapters and by including new sections on combinable crops, organic farming and nitrogen leaching. As in previous editions this book presents all the modern crop production methods in a comprehensive and easily understood manner. As such it should continue to be the standard textbook for all crop husbandry syllabi at all levels of agricultural teaching.